Group concept mapping to develop a salon-based HPV self-collection intervention - Kelly N. B. Palmer; Namoonga M. Mantina; Adebola Adegboyega; Itunu O. Sokale; Kathleen Pryor; Azaria Suero-Davis; Trevon Brooks; Jennifer Hatcher (Cancer Causes & Control, 2025)
Background Black women in the US face higher cervical cancer mortality rates due to delayed diagnoses linked to lower screening rates. Contributing factors include provider bias, costs, and limited access, particularly affecting women aged 40–64. While innovative approaches like clinical and home-based HPV self-collection exist, equitable dissemination remains challenging. Distributing HPV self-collection kits in unconventional sites like hair salons may offer a solution. Using concept mapping, we gathered community insights to design a salon-based cervical cancer screening intervention. Methods We employed groupwisdom™ and REDCap platforms for community-based participatory intervention development. Participants included members of the Black Community Advisory Council of Tucson (Black CACTus), comprising hairstylists ( n = 3), salon clients ( n = 4), and healthcare providers( n = 3), all identifying as Black women aged 23–53. Concept mapping included: 1) Brainstorming statements, 2) Sorting statements into thematic clusters, 3) Rating importance and feasibility, 4) Reviewing the cluster map, and 5) Evaluating a draft intervention. Results Brainstorming produced 39 statements, forming six clusters: 1) Program Promotion, 2) Insurance, Cost & Benefits, 3) Communication Considerations, 4) Information and Education, 5) Overall Logistics and Process, and 6) Sample Collection. Communication Considerations and Sample Collection were rated most important, with Communication Considerations also ranking highest for feasibility. Communication Considerations, Information and Education, and Sample Collection were the highest rated when importance and feasibility were considered together. Conclusions Engaging community perspectives is essential for adapting cancer screening from clinical settings to community spaces like hair salons. This collaborative concept mapping approach identified strategies to enhance cervical cancer screening access and uptake among Black women.

Toxicity of crude oil-derived polar unresolved complex mixtures to Pacific herring embryos: Insights beyond polycyclic aromatic hydrocarbons - Maxwell L. Harsha; Yanila Salas-Ortiz; Alysha D. Cypher; Ed Osborn; Eduardo Turcios Valle; Jacob L. Gregg; Paul K. Hershberger; Yuri Kurerov; Sarah King; Aleksandar I. Goranov; Patrick G. Hatcher; Anastasia Konefal; et al. (Science of The Total Environment, 2024)

Aggregation and Degradation of Dispersants and Oil by Microbial Exopolymers (ADDOMEx): Toward a Synthesis of Processes and Pathways of Marine Oil Snow Formation in Determining the Fate of Hydrocarbons - Antonietta Quigg; Peter H. Santschi; Chen Xu; Kai Ziervogel; Manoj Kamalanathan; Wei-Chun Chin; Adrian B. Burd; Andrew Wozniak; Patrick G. Hatcher (Frontiers in Marine Science, 2021)
Microbes (bacteria, phytoplankton) in the ocean are responsible for the copious production of exopolymeric substances (EPS) that include transparent exopolymeric particles. These materials act as a matrix to form marine snow. After the Deepwater Horizon oil spill, marine oil snow (MOS) formed in massive quantities and influenced the fate and transport of oil in the ocean. The processes and pathways of MOS formation require further elucidation to be better understood, in particular we need to better understand how dispersants affect aggregation and degradation of oil. Toward that end, recent work has characterized EPS as a function of microbial community and environmental conditions. We present a conceptual model that incorporates recent findings in our understanding of the driving forces of MOS sedimentation and flocculent accumulation (MOSSFA) including factors that influence the scavenging of oil into MOS and the routes that promote decomposition of the oil post MOS formation. In particular, the model incorporates advances in our understanding of processes that control interactions between oil, dispersant, and EPS in producing either MOS that can sink or dispersed gels promoting microbial degradation of oil compounds. A critical element is the role of protein to carbohydrate ratios (P/C ratios) of EPS in the aggregation process of colloid and particle formation. The P/C ratio of EPS provides a chemical basis for the “stickiness” factor that is used in analytical or numerical simulations of the aggregation process. This factor also provides a relative measure for the strength of attachment of EPS to particle surfaces. Results from recent laboratory experiments demonstrate (i) the rapid formation of microbial assemblages, including their EPS, on oil droplets that is enhanced in the presence of Corexit-dispersed oil, and (ii) the subsequent rapid oil oxidation and microbial degradation in water. These findings, combined with the conceptual model, further improve our understanding of the fate of the sinking MOS (e.g., subsequent sedimentation and preservation/degradation) and expand our ability to predict the behavior and transport of spilled oil in the ocean, and the potential effects of Corexit application, specifically with respect to MOS processes (i.e., formation, fate, and half-lives) and Marine Oil Snow Sedimentation and Flocculent Accumulation.

A bird's‐eye view of reservoirs in the Mississippi Basin tips a need for large‐scale coordination - Leandro E. Miranda; Giancarlo Coppola; Hunter R. Hatcher; Matthew B. Jargowsky; Zachary S. Moran; Michael C. Rhodes (Fish and Fisheries, 2021)
Reservoirs are mostly managed at local scales as spatially independent units. A basin‐scale perspective may increase awareness at a broader scope and generate insight not evident at local scales. We examined the array of reservoir attributes and fisheries in the Mississippi Basin to identify management opportunities. The basin is the third largest in the world and includes over 1,700 reservoirs >100 ha, the most of any river basin. Our bird's‐eye view shows a piecemeal approach where reservoirs are mostly administered at the local level. Basin‐wide or catchment coordination to holistically address problems that recur across the basin is mostly lacking. A basin‐wide coordination arrangement could facilitate various facets of reservoir management. We reviewed governance arrangements in major river basins across the globe and concluded that the basin‐wide administrative layer we encourage for the Mississippi Basin may already exist in some basins but may not be directly applicable everywhere.

Advancing impact prediction and hypothesis testing in invasion ecology using a comparative functional response approach - Jaimie T. A. Dick; Mhairi E. Alexander; Jonathan M. Jeschke; Anthony Ricciardi; Hugh J. MacIsaac; Tamara B. Robinson; Sabrina Kumschick; Olaf L. F. Weyl; Alison M. Dunn; Melanie J. Hatcher; Rachel A. Paterson; Keith D. Farnsworth; et al. (Biological Invasions, 2014)
Invasion ecology urgently requires predictive methodologies that can forecast the ecological impacts of existing, emerging and potential invasive species. We argue that many ecologically damaging invaders are characterised by their more efficient use of resources. Consequently, comparison of the classical ‘functional response’ (relationship between resource use and availability) between invasive and trophically analogous native species may allow prediction of invader ecological impact. We review the utility of species trait comparisons and the history and context of the use of functional responses in invasion ecology, then present our framework for the use of comparative functional responses. We show that functional response analyses, by describing the resource use of species over a range of resource availabilities, avoids many pitfalls of ‘snapshot’ assessments of resource use. Our framework demonstrates how comparisons of invader and native functional responses, within and between Type II and III functional responses, allow testing of the likely population-level outcomes of invasions for affected species. Furthermore, we describe how recent studies support the predictive capacity of this method; for example, the invasive ‘bloody red shrimp’ Hemimysis anomala shows higher Type II functional responses than native mysids and this corroborates, and could have predicted, actual invader impacts in the field. The comparative functional response method can also be used to examine differences in the impact of two or more invaders, two or more populations of the same invader, and the abiotic (e.g. temperature) and biotic (e.g. parasitism) context-dependencies of invader impacts. Our framework may also address the previous lack of rigour in testing major hypotheses in invasion ecology, such as the ‘enemy release’ and ‘biotic resistance’ hypotheses, as our approach explicitly considers demographic consequences for impacted resources, such as native and invasive prey species. We also identify potential challenges in the application of comparative functional responses in invasion ecology. These include incorporation of numerical responses, multiple predator effects and trait-mediated indirect interactions, replacement versus non-replacement study designs and the inclusion of functional responses in risk assessment frameworks. In future, the generation of sufficient case studies for a meta-analysis could test the overall hypothesis that comparative functional responses can indeed predict invasive species impacts.

Physical connectivity in the Mesoamerican Barrier Reef System inferred from 9 years of ocean color observations - I. Soto; S. Andréfouët; C. Hu; F. E. Muller-Karger; C. C. Wall; J. Sheng; B. G. Hatcher (Coral Reefs, 2009)

Characterizing the properties of dissolved organic matter isolated by XAD and C-18 solid phase extraction and ultrafiltration - Sara B. Schwede-Thomas; Yu-Ping Chin; Karl J. Dria; Patrick Hatcher; Edith Kaiser; Barbara Sulzberger (Aquatic Sciences, 2005)

Diagnostic radiation and the risk of multiple myeloma (United States) - Juliet L. Hatcher; Dalsu Baris; Andrew F. Olshan; Peter D. Inskip; David A. Savitz; G. Marie Swanson; Linda M. Pottern; Raymond S. Greenberg; Ann G. Schwartz; Janet B. Schoenberg; Linda Morris Brown (Cancer Causes & Control, 2001)

A 200-year coral stable oxygen isotope record from a high-latitude reef off Western Australia - H. Kuhnert; J. Pätzold; B. Hatcher; K.-H. Wyrwoll; A. Eisenhauer; L. B. Collins; Z. R. Zhu; G. Wefer (Coral Reefs, 1999)

Coral reef ecosystems: how much greater is the whole than the sum of the parts? - B. G. Hatcher (Coral Reefs, 1997)